Towards a global perspective on web tracking. Issue 87 (November 2019) - Samarasinghe, Nayanamana; Mannan, Mohammad
Abstract: Several past measurement studies uncovered various aspects of web-based tracking and its serious impact on user privacy. Most studies used institutional resources, e.g., computers hosted at well-known universities, or cloud-computing infrastructures such as Amazon EC2, confining the study to a particular geolocation or a few locations. Would there be any difference if web tracking is measured from actual user-owned residential machines? Does a user's geolocation affect web tracking? Past studies do not adequately answer these important questions, although web users come from across the globe, and tracking primarily targets home users. As a step forward, we leverage the Luminati proxy service to run a measurement study using residential machines from 56 countries. We rely on the OpenWPM web privacy measurement framework to analyze third-party scripts and cookies in 2050 distinct URLs (Alexa Top-1000 home pages and Alexa Top-50 country-specific home pages for all 56 countries, and shared URLs via Twitter from Alexa Top-1000 domains for 10 countries). Our findings reveal that the prevalence of web tracking varies across the globe. In addition to location, tracking also seems to depend on factors such as data privacy policies, Internet speed and censorship. We also observe that despite legal efforts for strengthening privacy, such as the EU cookie law, violations are common and very blatant in some cases, highlighting the need for more effective tools and frameworks for compliance monitoring and enforcement.